2023
DOI: 10.1002/cnr2.1829
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life (QOL) in cancer patients attending oncology unit of aTeaching Hospital in Bangladesh

Nazmul Islam,
Alok Atreya,
Samata Nepal
et al.

Abstract: BackgroundThe quality of life (QoL) of a cancer patient is their perception of their physical, functional, psychological, and social well‐being. QoL is one of the most important factors to consider when treating someone with cancer and during follow‐up. The aim of this study was to understand the state of QoL among cancer patients in Bangladesh and to determine the factors that affect it.MethodsThis cross‐sectional study was conducted on 210 cancer patients who attended the oncology unit of Delta Medical Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Another important factor was the stage of cancer, which was found to be a significant factor in QoL, with participants with stage III and IV cancer being 86% and 84% less likely, respectively, to have a good QoL compared to those with stage I cancer. This report is supported by a study from Bangladesh, indicating that functional scales decline while dyspnea and insomnia worsen as the cancer advances ( 42 ). In fact, as cancer progresses, the patients’ condition typically deteriorates due to factors such as tumor growth, metastasis, and the side effects of cancer treatments ( 43 ).…”
Section: Discussionsupporting
confidence: 73%
“…Another important factor was the stage of cancer, which was found to be a significant factor in QoL, with participants with stage III and IV cancer being 86% and 84% less likely, respectively, to have a good QoL compared to those with stage I cancer. This report is supported by a study from Bangladesh, indicating that functional scales decline while dyspnea and insomnia worsen as the cancer advances ( 42 ). In fact, as cancer progresses, the patients’ condition typically deteriorates due to factors such as tumor growth, metastasis, and the side effects of cancer treatments ( 43 ).…”
Section: Discussionsupporting
confidence: 73%
“… 83 All functional scales in this study were higher than those reported among Bangladeshi patients with cancer, which was also reflected by the low global health status score of 48.85 (SD = 19.38). 84 On the other hand, a study that was conducted in Nepal reported a higher mean global health status among Nepali cancer patients (83.3 ± 17.70) despite a high mean financial burden score (68.02 ± 33.81). 85 …”
Section: Discussionmentioning
confidence: 96%
“…Although various studies presented the results of LE and WW in treating patients with locally advanced rectal cancer, reliable data comparing the outcomes of these two approaches are still lacking [ 29 ]. In part, the reason WW and LE are difficult to compare is the need to consider different outcomes, including survival, relapses, and QoL variables [ 30 , 31 ]. In this framework, the win statistics could easily consider both classical efficacy and QoL outcomes, providing a comprehensive evaluation of treatment benefits and drawbacks.…”
Section: Methodsmentioning
confidence: 99%